Shoring and its application a handbook for the use of students - Blagrove, George H. (Crosby Lockwood, 1887)
This title covers the construction of shoring to support buildings during alteration and to protect dangerous structures from collapse, and concludes with chapters on underpinning and straightening walls.
Includes index.
Keywords: Shoring and underpinning.; elektronické knihy; electronic books